Learning in action and adventure sports. Issue 2 (3rd May 2016) - Ellmer, Eva; Rynne, Steven
ABSTRACT: The exponential growth in action and adventure sport (e.g. snowboarding, bicycle motorcross (BMX), surfing, parkour) participation over the past two decades has been showcased in world championship events and the inclusion in Olympic programs. Yet, by virtue of their alternative, escapist and/or adventure-based origins, these sports do not fully conform to the characteristics by which traditional sports are known (e.g. structured training). An area of great interest across all sports is how athletes learn to perform. In action and adventure sports, the lack of well-established, sport-specific knowledge bases mean that athletes potentially learn in different ways. This research seeks to make an initial contribution to our understanding by examining the learning trajectory of an international-level Trials athlete. She was found to take a strong role in her own learning while leveraging her coach and peers for learning opportunities at different stages of her career to date. Suggestions for future research in this area are subsequently offered.